“Comunidades tradicionais”: uso e apropriação do território em ilhas federais do rio Uraricoera-RR - Rodrigues, Vivian Karinne Morais (2016)
This research analyzes the forms of use and appropriation of land in coastal environments in Uraricoera river, taking to support the study of the territory, territoriality and traditional communities. The objective is to understand the spatial practices of "ilheiros" (occupants of the islands) and their participation in territorial production process. This goal leads us to reflect on the forms of use and appropriation of the islands inhabitants of the territory reveal specific territoriality? Since the islands are occupied and differentially used by different subjects. We analyzed multiple dimensions of the social universe of the occupants of the islands: political, social, economic and symbolic. It conducted a literature review and documentation relevant to the theme, combining theory with empirical, field work with the use of specific methodologies such as participatory mapping, from the appreciation of the territorial perception of the local community, using geoprocessing techniques as use of GPS (Global Positioning System) and interviews. The survey results reveal a variety of forms of natural resource use and occupation of the territory, since the islands there are locals who have no relationship with the living environment and residents living exclusively from the exploitation of natural resources of the area. Also revealed that fishing in the river Uraricoera has specific territoriality that comes the way of how the fishermen use the resources of the river, where they establish a set of own rules expressing the sense of appropriation and power.